Effects of various host plants on nutritional indices and some biochemical compounds in green oak leaf roller, Tortrix viridana L. (Lepidoptera: Tortricidae) - H. Yazdanfar; M. Ghodskhah Daryaei; J. Jalali Sendi; H. Ghobari; B. Valizadeh (Journal of Entomological and Acarological Research, 2015)
The green oak leaf roller, Tortrix viridana L., is one of the most destructive pests, causing damages to various species of oak, feeding on different host plants including Quercus infectoria Oliv, Q. branti Lindl, and Q. libani Oliv. Nutritional indices, activity of enzymatic and non-enzymatic compounds of T. viridana were studied under laboratory conditions. In addition, chemical components were analysed in the leaves of the three host plants. Fourth instar larvae reared on Q. branti showed the highest values of relative consumption rate (RCR), approximate digestibility, and consumption index (48.73±6.22; 90.45±1.06 and 97.45±12.44 respectively), while the lowest values were observed on Q. libani. Efficiency of conversion of ingested food in the fourth instar larvae was the highest (3.17±0.661) on Q. libani and the lowest (1.53±0.164) on Q. branti. The fifth instar larvae fed on Q. libani had the highest RCR (15.64±2.51). The highest amounts of triglycerides, uric acid, glucose, protein and the lowest activity of alkaline phosphatase were observed in the fifth instar larvae reared on Q. libani. The leaves of Q. libani highlighted the highest amounts of total nitrogen, total protein, water, potassium, magnesium and total carbohydrate. The present research suggested that the nutritional quality of the host plants have crucial effects on T. viridana larvae.